2018
DOI: 10.1136/bmjopen-2018-021486
|View full text |Cite
|
Sign up to set email alerts
|

Mixed methods process evaluation of an enhanced community-based rehabilitation intervention for elderly patients with hip fracture

Abstract: ObjectivesTo describe the implementation of an enhanced rehabilitation programme for elderly hip fracture patients with mental capacity, in a randomised feasibility study compared with usual rehabilitation. To compare processes between the two and to collect the views of patients, carers and therapy staff about trial participation.DesignMixed methods process evaluation in a randomised feasibility study.SettingPatient participants were recruited on orthopaedic and rehabilitation wards; the intervention was deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Overcoming barriers in gaining dedicated SIL time may be a prime way to enhance future consistency in implementation. Staff availability has been identified as a factor in other process evaluations related to hip fracture patients 43 45…”
Section: Discussionmentioning
confidence: 99%
“…Overcoming barriers in gaining dedicated SIL time may be a prime way to enhance future consistency in implementation. Staff availability has been identified as a factor in other process evaluations related to hip fracture patients 43 45…”
Section: Discussionmentioning
confidence: 99%
“…This study suggested that the support provided to Brain-in-Hand users was as important as the app itself. Although implementation [36][37][38] and influencing rehabilitation outcomes, 39 and are some of the known challenges and barriers to implementation. [14][15][16] However, there is limited evidence supporting the interaction between the 'Big T' and the 'small t', with many studies focussing only on the environmental context (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Realist evaluation is a theory-driven approach to understanding for whom and in what circumstances complex interventions work [ 16 ] and has been used for studying a number of complex interventions, including health information technology [ 17 ]. Realist approaches can be used both to evaluate complex interventions and inform intervention design [ 18 ]. For these reasons, a realist approach is highly appropriate for the conduct of this review.…”
Section: Methodsmentioning
confidence: 99%